2012
DOI: 10.5812/hepatmon.6035
|View full text |Cite
|
Sign up to set email alerts
|

Age-Specific Seroprevalence of Anti-Hepatitis A Antibody Among 1-30 Years Old Population of Savadkuh, Mazandaran, Iran With Literature Review

Abstract: BackgroundTo determine age-specific seroprevalence rates of hepatitis A virus (HAV) immunoglobulin G (IgG) antibody in Savadkuh district, Mazandaran province, north of Iran, as well as to compare the collected data with earlier seroprevalence studies in the region and Iran in order to draw a proper epidemiological pattern for HAV infection in the country.ObjectivesThis study aimed to assess an age-specific HAV seroprevalence among 1- to 30-yearold people in Savadkuh, a less developed district of Mazandaran provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 20 publications
3
22
0
Order By: Relevance
“…The seroprevalence of HAV in Turkey varies among geographical regions, but most regions have an intermediate endemicity [6,7]. HAV infections can be prevented by immunization and HAV vaccine may be used for prophylaxis [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The seroprevalence of HAV in Turkey varies among geographical regions, but most regions have an intermediate endemicity [6,7]. HAV infections can be prevented by immunization and HAV vaccine may be used for prophylaxis [5].…”
Section: Introductionmentioning
confidence: 99%
“…Since, most infections, especially in children, are subclinical, we can estimate HAV infection prevalence in a population by determination of the anti-HAV antibodies [4]. The distribution of anti-HAV antibody seroprevalence over several age groups can be used as a marker of a useful HAV epidemiologic pattern relating to viral transmission through a community [5]. Serologic studies help to determine the patterns of endemicity which have been identified as low, medium and high.…”
Section: Introductionmentioning
confidence: 99%
“…Table 3 shows the seroprevalence of hepatitis A in different parts of Iran. In Saffar et al's study on HAV seroprevalence in individuals aged 1 to 30 years in Savadkooh, the data showed that the anti-HAV seroprevalence rate increased significantly with age from 5.7% in the age group of 1 to 2.9 years to 34.8% in adolescents (24). Altogether, studies by Alian et al (16), Mehr et al (17), and Sofian et al (18) in different parts of Iran and on various age groups showed inconsistencies in seroepidemiology of HAV between different age groups and within the same age group of different regions.…”
Section: Discussionmentioning
confidence: 99%
“…Available data documented that the risk of death due to HAV infection in patients with underlying chronic liver disease was 23 times more than those without chronic liver disease (11). On the other hand in recent years, a few studies from developing countries reported a changing trend of HAV epidemiology with shift to intermediate or low endemicity, because of improved sanitary condition and hygiene practices (6,(12)(13)(14)(15). Due to absence of HAV vaccination, Iran was previously considered a country with hyperendemic hepatitis A infection.…”
Section: Introductionmentioning
confidence: 99%
“…Due to absence of HAV vaccination, Iran was previously considered a country with hyperendemic hepatitis A infection. The studies in Iran indicate that HAV infection is decreasing, especially in children (13,16,17). Based on the obtained information, mass immunization of all children could be suggested, but there are also barriers such as cost and feasibility; therefore, considering these problems, at least vaccination in high risk children, such as those with chronic liver diseases, can be recommended.…”
Section: Introductionmentioning
confidence: 99%